RANCANG BANGUN TEACHING AID ELEKTRO PNEUMATIK - Rachmad Ikhsan; Yeni Yanti (J-Innovation, 2019)
One result of technology that has been used in education is a medium or a tool of learning resources that are useful tocontribute a role in the learning process. So at this project was designed of a Teaching aid for practical electro-pneumaticautomation industry in the laboratory. Teaching aid also comes with a Schneider PLC twido that serves as controller forthe next command control system according to the program designed. To simplify the user, teaching aid is also equippedwith banana plug socket as the connector is used when teaching aid, teaching aid is also equipped with a manual whichformed jobsheet which includes some examples and practice questions as a guideline when teaching aid is used. In thepresence of teaching is expected to assist students in the learning process.